2016
DOI: 10.1002/crat.201600222
|View full text |Cite
|
Sign up to set email alerts
|

Strontium titanate: From symmetry changes to functionality

Abstract: Pure strontium titanate exhibits a cubic perovskite-type structure at room temperature, but many approaches to break this high degree of symmetry are accessible. The present review summarizes some possible methods by discussing the effects of stoichiometry variation, ion implantation, temperature treatment and external electric fields. Since oxygen vacancies are the most prominent and most mobile defect species in strontium titanate, they play a crucial role also for structural changes due to external influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…This ferroelectricity can be stabilized by a variety of external factors such as compressive strain, which allows the investigation of the ferroelectric phase at much higher temperatures. Here, our chamber was used to conduct a resonant XRD experiment at different low temperatures between 96 K and 300 K at nine oblique Bragg reflections to study an expected structural relationship (Nentwich et al, 2021) to a recently discovered piezo-and pyroelectric phase, the so-called migration-induced fieldstabilized polar (MFP) phase (Khanbabaee et al, 2016;Hanzig et al, 2013Hanzig et al, , 2015Stö cker et al, 2017) with the resonantly suppressed diffraction (RSD) approach (Richter et al, 2018). This new method allows sub-picometre precision by analyzing a purposely induced intensity minimum of an research papers energy-dependent Bragg reflection.…”
Section: Synchrotron Studies Of Functional Materials At Low Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…This ferroelectricity can be stabilized by a variety of external factors such as compressive strain, which allows the investigation of the ferroelectric phase at much higher temperatures. Here, our chamber was used to conduct a resonant XRD experiment at different low temperatures between 96 K and 300 K at nine oblique Bragg reflections to study an expected structural relationship (Nentwich et al, 2021) to a recently discovered piezo-and pyroelectric phase, the so-called migration-induced fieldstabilized polar (MFP) phase (Khanbabaee et al, 2016;Hanzig et al, 2013Hanzig et al, , 2015Stö cker et al, 2017) with the resonantly suppressed diffraction (RSD) approach (Richter et al, 2018). This new method allows sub-picometre precision by analyzing a purposely induced intensity minimum of an research papers energy-dependent Bragg reflection.…”
Section: Synchrotron Studies Of Functional Materials At Low Temperaturesmentioning
confidence: 99%
“…The presented sample environmental chamber was recently used for the combined variation of temperature and electric field during the study of structural symmetry reduction in the MFP phase of SrTiO 3 (Hanzig et al, 2013(Hanzig et al, , 2015Khanbabaee et al, 2016;Stö cker et al, 2017). The application of approximately 1 MV m À1 causes a structural transition of cubic SrTiO 3 with space group Pm 3 3m ð221Þ (Hanzig et al, 2013) to a P4mm tetragonal structure with elongated c direction accompanied by a polar distortion of the TiO 6 octahedra in the field direction (Richter et al, 2018).…”
Section: Synchrotron Study Of the Electroformation Of Strontium Titanmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Stocker et al's. 27 study on symmetry changes of strontium titanate suggested that structural phase transition occurs where this cubic structure of strontium titanate became tetragonal structure when temperature of 105 K or above was supplied (from hot press compression molding). The phase change phenomenon increases the chances of large spontaneous polarization which distinctively could have increased the dielectric permittivity of the composite.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Strontium titanate (SrTiO 3 ) is, due to its ability to incorporate and transport oxygen, a promising candidate for such systems . Furthermore, the unique defect chemistry of SrTiO 3 is known to be responsible for peculiar new properties like pyroelectricity and acting as an all‐solid battery . Despite those technological applications, however, SrTiO 3 is one of the most important mixed‐conducting electroceramics, which has often been used as a model system in surface physics and defect chemistry in general .…”
Section: Introductionmentioning
confidence: 99%